MICU2 up-regulation enhances tumor aggressiveness and metabolic reprogramming during colorectal cancer development. - Alison Robert; David Crottès; Jérôme Bourgeais; Naig Gueguen; Arnaud Chevrollier; Jean-François Dumas; Stéphane Servais; Isabelle Domingo; Stéphanie Chadet; Julien Sobilo; Olivier Hérault; Thierry Lecomte; et al. (PLoS Biology)
The mitochondrial Ca2+ uniporter (MCU) plays crucial role in intramitochondrial Ca2+ uptake, allowing Ca2+-dependent activation of oxidative metabolism. In recent decades, the role of MCU pore-forming proteins has been highlighted in cancer. However, the contribution of MCU-associated regulatory proteins mitochondrial calcium uptake 1 and 2 (MICU1 and MICU2) to pathophysiological conditions has been poorly investigated. Here, we describe the role of MICU2 in cell proliferation and invasion using in vitro and in vivo models of human colorectal cancer (CRC). Transcriptomic analysis demonstrated an increase in MICU2 expression and the MICU2/MICU1 ratio in advanced CRC and CRC-derived metastases. We report that expression of MICU2 is necessary for mitochondrial Ca2+ uptake and quality of the mitochondrial network. Our data reveal the interplay between MICU2 and MICU1 in the metabolic flexibility between anaerobic glycolysis and OXPHOS. Overall, our study sheds light on the potential role of the MICUs in diseases associated with metabolic reprogramming.